The Relationship between Academic Stress with Coping Mechanism of PSSKPN Students of Udayana University - Hasugian, Flora Maranatha; Suarningsih, Ni Kadek Ayu; Saputra, I Kadek (Journal of A Sustainable Global South; Vol 7 No 1 (2023): February 2023DO - 10.24843/jsgs.2023.v07.i01.p01, 2023)
The academic education process faced by nursing students is a source of considerable stressors to trigger academic stress. Academic stress would affect the way they deal with the stressors that called coping mechanism response. This study was correlative research with cross sectional approach. This study consisted of 57 respondents obtained by total sampling technique. The data collection was used academic stress questionnaire and ways of coping questionnaire to identified respondent characteristics, academic stress and coping mechanism. This study showed there was a significant correlation between academic stress with the coping mechanism ( p <0.05; r= 0.517). The correlation was negative and had a medium strength, which means when the academic stress gets higher, the coping mechanism gets lower. This study is expected to be an evaluation for students, education institutions, and nurses as health workers. Actions to reduce academic stress and improve adaptive coping mechanism also expected could be carried out.